Scriptural interpretation and community self-definition in Luke-Acts and the writings of Justin Marty r - Wendel, Susan J. (Novum Testamentum, Supplements, 2011)
Scholars of Christian origins often regard Luke-Acts and the writings of Justin Martyr as similar accounts of the replacement of Israel by the non-Jewish church. According to this view, both authors commandeer the Jewish scriptures as the sole possession of non-Jewish Christ-believers, rather than of Jews. Offering a fresh analysis of the exegesis of Luke and Justin, this book uncovers significant differences between their respective depictions of the privileged status that Christ-believers hold in relation to the Jewish scriptures. Although both authors argue that Christ-believers alone possess an inspired capacity to interpret the Jewish scriptures, unlike Justin, Luke envisages an ongoing role for the Jewish people as recipients of the promises that God pledged to Israel.